2022
DOI: 10.1007/s10530-022-02741-6
|View full text |Cite
|
Sign up to set email alerts
|

The role of weed seed contamination in grain commodities as propagule pressure

Abstract: The international grain trade is a major pathway for the introduction of alien plants because grain commodities can be contaminated with various weed seeds. To evaluate how alien weed seeds derived from imported grain commodities affect local vegetation in international trading ports, we conducted a vegetation survey on a set of grain landing ports and non-grain landing ports in nine regions throughout Japan to compare the vegetation between these two types of ports. We also surveyed weed seed contamination of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…4,82 Consequently, gene flow between crops (or volunteer plants) and their wild or weedy relatives may lead to the introgression of desired crop traits in wild/ weedy populations, and thus result in the evolution of new weeds or enhance the weediness of existing weeds (more problematic weeds), referred to as "superweeds". 4,83 In addition, given that seeds of cultivated species could be intentionally or unintentionally dispersed away from the production areas, 17,18 superweeds may emerge in those countries where desired crop traits have been permitted legally or in those where they have not. 82,84,85 For example, Pandolfo et al 8 found transgenic glyphosate-resistant oilseed rape in Argentina where it has never been permitted legally.…”
Section: The Design Of Second-generation Crops and Their Impact On Weedsmentioning
confidence: 99%
See 2 more Smart Citations
“…4,82 Consequently, gene flow between crops (or volunteer plants) and their wild or weedy relatives may lead to the introgression of desired crop traits in wild/ weedy populations, and thus result in the evolution of new weeds or enhance the weediness of existing weeds (more problematic weeds), referred to as "superweeds". 4,83 In addition, given that seeds of cultivated species could be intentionally or unintentionally dispersed away from the production areas, 17,18 superweeds may emerge in those countries where desired crop traits have been permitted legally or in those where they have not. 82,84,85 For example, Pandolfo et al 8 found transgenic glyphosate-resistant oilseed rape in Argentina where it has never been permitted legally.…”
Section: The Design Of Second-generation Crops and Their Impact On Weedsmentioning
confidence: 99%
“…Alien species are introduced intentionally (for example, for cultivation, breeding, and research) or accidentally (for example, as contaminants of traded goods) outside their native range through global commerce 17 . Internationally traded seed and grain are two of the main pathways for the introduction of weed seeds into new areas 17,18 . So, weeds can be problematic in their native range (“native weeds”) and/or colonize new habitats and become “invasive weeds”.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seeds are a key agricultural input and output and are a part of a complex global trade network 1,10 . However, as a global commodity, contaminated seed for sowing can provide a pathway for the introduction and establishment of pests, weeds and diseases with the potential to cause unwanted impacts across field, farm, regional or national scales 1–3 . These unintended introductions contribute to the homogenization of world floras and are a threat to global food security.…”
Section: Introductionmentioning
confidence: 99%
“… 1 , 10 However, as a global commodity, contaminated seed for sowing can provide a pathway for the introduction and establishment of pests, weeds and diseases with the potential to cause unwanted impacts across field, farm, regional or national scales. 1 , 2 , 3 These unintended introductions contribute to the homogenization of world floras and are a threat to global food security. Mitigating the impacts of weeds, pests, diseases or other invasive species in seed‐for‐sowing systems is a shared goal of farmers, seed producers and national/international plant protection organizations.…”
Section: Introductionmentioning
confidence: 99%